2016
DOI: 10.3151/jact.14.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Types of Waste Wood Species on the Hydration Characteristic of Portland Cement

Abstract: Despite much work on wood-cement composites, effects of wood species on the hydration of cements remain unclear until now. Thus, we herein investigated systematically effects of two typical wood species wastes on the hydration of Portland cement in this work. It was found that adding the poplar flour prominently affects the formation of the calcium silicate hydrate gel (C-S-H gel) delaying the hydration process, while the Chinese fir flour hardly retards the process due to different components. Compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This result supports the more significant suppressing effect when chlorella is introduced in cement as compared to spirulina. A similar effect of wood flour in Portland cement at 7.5 wt % (wood flour/dry cement) was reported by Dong et al 73 They showed that the wood with high content of sugar and sugar acid (poplar wood) inhibits the hydration process more than the Chinese fir (lower content of sugar and sugar acid). However, they reported that ettringite generation was not negatively affected by the presence of wood flour in either case, which agrees with our findings.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…This result supports the more significant suppressing effect when chlorella is introduced in cement as compared to spirulina. A similar effect of wood flour in Portland cement at 7.5 wt % (wood flour/dry cement) was reported by Dong et al 73 They showed that the wood with high content of sugar and sugar acid (poplar wood) inhibits the hydration process more than the Chinese fir (lower content of sugar and sugar acid). However, they reported that ettringite generation was not negatively affected by the presence of wood flour in either case, which agrees with our findings.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…Chinese fir particles for the production of CBPB were adjusted to a moisture content (MC) of 12±1.0% in an oven (DKN611, Yamato Company, Japan) at the temperature of 103±2°C. Portland cement applied in this study was produced by Shanggan cement plant of Lin'an, Zhejiang Province, China, with its chemical compositions and mineral compositions cited by Wang et al (2012), and Dong et al (2016). CaCl 2 , purchased from Hangzhou Gaojing Fine Chemical Co., Ltd, Hangzhou, China, was used as the cement curing accelerator.…”
Section: Methodsmentioning
confidence: 99%
“…For the production of wood-cement composites such woodworking wastes and organic components as straw, nutshell, sludge, foam, various wastes, etc are used [13][14][15][16][17][18][19][20][21]. Portland cement is used as astringent but the following additives as accelerators and plasticizers are allowed [22].…”
Section: Introductionmentioning
confidence: 99%